Materials for Tribology’s Application: A Mini Analysis - Norazlianie, Sazali; Nor Hasrul Akhmal, Ngadiman (Akademi Baru, 2020)
The exploitation of advanced material in a miscellaneous area can improve the performance and value of material engineering. The tribological applications are analyses based on the natures of materials utilized, for example, polymers, and polymer composite also ceramics, and ceramic composites. Specifically, the study on the behaviour of polymer-composite, surface interaction and polymer are due to the development of the composite nowadays become widely attention and noticeable worldwide in various industry. In conjunction, the friction effect on those materials is not directly relatable with the material characteristic but based on their tribology behaviour. The friction is not directly influencing the material characteristic but has affected the tribology behaviour of the material.